The history of the Galician Division of the Waffen-SS. Volume 2. Stalin's nemesis - Melnyk, Michael James (The history of the Galician Division of the Waffen-SS, 2016)
„The History of the Galician Division of the Waffen SS – Volume Two: Stalin’s Nemesis is the second volume of a two-part set on the history of the Galician Division based on twenty-five years’ research by historian Michael James Melnyk. The author has sourced additional new and hitherto unseen original material on all aspects of the Division’s history from archives and private collections in Europe, Australia, North American and Canada. Complemented by individual accounts and contributions of many veterans, which add an engaging personal dimension, this definitive account is lavishly illustrated with many unique photos and crammed full of details, notes and references.” -- Publisher's description